(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main causes of structural failure are imperfect designs that haven’t determined the factual loading conditions on the structural rudiments. Damages from earthquake generally begin at locations of structural weaknesses in multi-storied framed structures. Structures with openings in slabs are prone to damages due to the action of side loads. These days, openings in the floors is common for numerous reasons like stair cases, lighting architectural etc., these openings in diaphragm causes stresses at discontinues joints with structure rudiments. Discontinuous diaphragms are designed without stress computations and are allowed about to be acceptable ignoring any gap goods. A Diaphragm is structural element that transmits side loads to the perpendicular resisting rudiments of a structure. The diaphragm forces tend to be transferred to the perpendicular resisting element primarily through in shear stress. The most common side loads to be defied are those performing from wind and earthquake conduct, but other side loads similar as side earth pressure or hydrostatic pressure can also be resisted by diaphragm action. The diaphragm of a structure frequently does double duty as the bottom system or roof system in a structure or the deck of the ground, which simultaneously supports gravity loads. Hence, the main aim of the present study is to do seismic analysis by the method of push- over analysis of steel multi-storied structure with varying diaphragm positions. In this work, openings in slabs are provided at various locations and with structures having different shaped columns are used. This entire project is done in ETABS Software.